The effect of Maqasid Al-Shariah towards youth motivation to become entrepreneur in Indonesia - Baharuddin, Gunawan; Riskarini, Dian; Widyastuti, Sri; Azzahra, Fatima (International Journal of Financial, Accounting, and Management, 2025)
Purpose: The article emphasizes the role of maqasid al-shariah as youth motivation towards the intention to be an entrepreneur. Method: This study is a quantitative research that collects data from 556 students across Indonesia and analyzes it through the Smart PLS statistical program to obtain results in both factor/indicator measurement and path analysis measurement. Results: The study found that maqasid al-shariah significantly affects the youth’s intention to become entrepreneurs. The sequence of the five maqasid al-shariah indicators, from the most dominant influence, is progeny, wealth, intellect, soul, and faith. Conclusions: This research provides valuable insight into the impact of Islamic principles, especially the Maqasid al-Shariah framework, on shaping entrepreneurial interests among university students. The emphasis on progeny and wealth reflects a dual commitment to maintaining family financial stability and contributing to community welfare through charitable efforts. Limitations: This study focuses solely on university students in Indonesia, potentially limiting the generalizability of the findings to other demographic groups. Additionally, reliance on self-reported data may introduce response or social desirability biases. Future research should adopt longitudinal approaches and more diverse samples to improve external validity.   Contribution: This study enriches research on maqasid al-shariah as a framework shaping religious motivation for entrepreneurship, an area that has not been widely explored. The findings also have implications for public policy and education, suggesting the integration of Islamic values into university curricula to enhance entrepreneurial character.